MANTIKÎ KIYAS İLE FIKHÎ KIYASIN KARŞILAŞTIRILMASI - Nazim Hasırcı (İslami İlimler Dergisi)
In this article in which logical syllogism and Juridical Qıyas are compared two reasoning types are first researched with the main lines, and then compared. It is seen that these two reasoning are resembled each other, but they are different from the stand point of form, content and the value of the result. At the same time, it is determined that Juridical Qıyas can be reduced to (transformed into) logical syllogism.